Spatial Configuration of the Argentine folklore in "Selecciones Folklóricas Codex" (1965-66) - T. Tuninetti, Ángel (Revista General de Información y Documentación, 2012)
During the 1960’s in Argentina, the impact of the folklore of the hinterlands in the capital, Buenos, Aires reached its peak, principally regarding music. The Selecciones Folklóricas, a peculiar and short-lived magazine, belong to this period. It was published in Buenos Aires from 1965 to 1966, and only 13 monthly issues appeared. The director was Augusto R. Cortázar, the most prominent scholar on Argentine folklore. The magazine was subtitled “A Readable, Documented and Visual Synthesis of the Traditional and Popular Argentina”, and it was conceived as a way of rescuing and promoting folkloric manifestations, fearing that progress would make them disappear. The Selecciones Folklóricas are an unique example of the way in which the metropolis defined and imagined the culture of the provinces.